2021
DOI: 10.2174/1570159x19666210211150856
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phenytoin, Phenobarbital Carbamazepine, Levetiracetam Lamotrigine and Valproate in Pregnancy and Breastfeeding: Risk of Major Malformations, Dose-dependency, Monotherapy vs Polytherapy, Pharmacokinetics and Clinical Implications

Abstract: : It is challenging to balance the fetal risks associated with the use of antiepileptic drugs (AEDs) against maternal and fetal risks of seizure worsening and therefore it is very important to define and distinguish the possible risks entailed by different AEDs. This paper aims to undertake a comprehensive review regarding the possible risks of four classical (phenytoin, carbamazepine, phenobarbital and valproate) and two newer (lamotrigine and levetiracetam) AEDs during pregnancy. The review focuses on major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 97 publications
0
31
0
1
Order By: Relevance
“…Although there are studies showing that CBZ causes malformations in the fetus, such as growth retardation, hypothyroidism, thrombocytopenia, mental retardation, immunoendocrine disorders, heart defects, and neural tube defects, 22,27,29,42,43 there are also pregnancy registry studies showing that it does not increase the risk of fetal malformation 44 …”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies showing that CBZ causes malformations in the fetus, such as growth retardation, hypothyroidism, thrombocytopenia, mental retardation, immunoendocrine disorders, heart defects, and neural tube defects, 22,27,29,42,43 there are also pregnancy registry studies showing that it does not increase the risk of fetal malformation 44 …”
Section: Discussionmentioning
confidence: 99%
“…An increased dosage of sodium valproate and topiramate is associated with even more incidence of significant congenital morbidities. Multidrug therapy, including medications like sodium valproate and topiramate, results in a higher incidence of significant morbidities [33]. Assessing risk patterns of other antiepileptics by referring to consistent research studies, the least number of malformations are observed with lamotrigine and levetiracetam, which include no or slight incidences of structural deformities, no organ-centric deformities except for an increased incidence of oral clefts in single drug therapy of lamotrigine, but this is not observed in all studies.…”
Section: Prevention and Reduction Of Sodium Valproate Usage In Pregna...mentioning
confidence: 99%
“…RID is a function of MP ratio and maternal drug clearance, and the safety threshold is 5–10%. However, RID higher than 10% is not necessarily a taboo for breastfeeding ( 18 , 19 ). It should be noted that M/P ratio is not necessarily proportional to RID.…”
Section: Metabolic Pathway Of Asms and The Influence Of Asms In Human...mentioning
confidence: 99%
“…M/P ratio ranging from 0.18–0.45 and RID ranging from 0.6–7.7% ( 20 ). The evaluation of adverse reactions in infants exposed to phenytoin through breast milk found that in most cases, there were no serious adverse reactions ( 19 ). There a report that breastfeeding under treatment with phenytoin led to methemoglobinemia ( 28 ).…”
Section: Metabolic Pathway Of Asms and The Influence Of Asms In Human...mentioning
confidence: 99%